Foucault, Buddhism and Disciplinary Rules - Voyce, Malcolm (Taylor and Francis, 2016)
Cover -- Title -- Copyright -- Contents -- Acknowledgements -- Notes on the text -- 1 Introduction to the work of Foucault and its use in this study -- 2 An overview of the Vinaya -- 3 The presentation of the Vinaya within forms of Western scholarship -- 4 The Vinaya and the Dharmaśāstra -- 5 The formation of the religious body -- 6 From ethics to aesthetics -- 7 The role of confession and discipline -- 8 Rules and transgressions -- 9 Conclusion: the 'care of the self' and the practice of the Vinaya -- Appendix: an outline of rules of the Pātimokkha -- Abbreviations -- Bibliography -- Index